The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1128/aem.29.1.125-127.1975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polychlorinated Biphenyl Formulations on the Growth of Estuarine Bacteria1

Abstract: Polychlorinated biphenyl formulations inhibited the growth of certain estuarine bacteria. The sensitive strains, although exhibiting some similar physiological characteristics, contained both gram-positive and gram-negative bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The available informnation relating to PCB and PHE stress on heterotrophic bacterial pop-ulation indicates variable, but minor, stress effects. In examining the effects of PCB on pure cultures of environmental isolates, PCB has demonstrated both inhibitory and stimulatory effects (6,7,20,27). In a sense, this investigation supports both types of observations.…”
Section: Discussionsupporting
confidence: 75%
“…The available informnation relating to PCB and PHE stress on heterotrophic bacterial pop-ulation indicates variable, but minor, stress effects. In examining the effects of PCB on pure cultures of environmental isolates, PCB has demonstrated both inhibitory and stimulatory effects (6,7,20,27). In a sense, this investigation supports both types of observations.…”
Section: Discussionsupporting
confidence: 75%
“…Others have shown that PCBs inhibited growth ofselected pure cultures ofbacteria when added to liquid growth medium (2). Sensitivity of bacteria at PCB concentrations lower than 1 mg/liter (1 ppm) has not commonly been reported, however, and information concerning the physiological basis of PCB toxicity in bacteria is meager.…”
mentioning
confidence: 99%
“…The relationship between increasing organic toxicant concentration and lag time has been observed in bacterial species capable of biodegrading other compounds. These include bacterial species capable of degrading p-nitrophenol (Wiggins and Alexander 1988), polychlorinated biphenyls (Bourquin and Cassidy 1975), and a variety of agricultural pesticides (Parker and Doxtader 1982;Lappin et al, 1985). The lag time noted prior to observable degradation is believed to be a function of both the time required for acclimation and the accumulation of sufficient microbial biomass to obtain measurable rates (Topp et al, 1988).…”
Section: Discussionmentioning
confidence: 99%